THE IMPACT OF PSYCHOSOCIAL SUPPORT ON THE QUALITY OF LIFE OF PATIENTS WITH DEGENERATIVE DISEASES: A SYSTEMATIC REVIEW OF HOLISTIC NURSING APPROACHES - Sri Wianti; Wijayanti Wijayanti; Lilis Lismayanti (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Degenerative diseases exert profound multidimensional impacts on patients’ lives, affecting not only their physical health but also psychological, social, and spiritual well-being. Conditions such as Parkinson’s disease, Alzheimer’s disease, and chronic kidney disease often compromise individuals’ adaptive capacity and impose considerable emotional and social burdens. Psychosocial support has emerged as a vital component of holistic nursing care, strengthening coping mechanisms, reducing stress, and enhancing overall well-being. However, existing evidence on its effectiveness remains fragmented and limited across different degenerative conditions. This study aims to examine the effect of psychosocial support on the quality of life of patients with degenerative diseases through a holistic nursing approach. A systematic literature review was conducted in accordance with the PRISMA 2020 guidelines using the Scopus database. The search employed keywords such as “psychosocial support”, “degenerative disease”, and “quality of life”, covering publications from 2010 to 2025. A total of 39 high-quality studies were selected from 5,217 retrieved records. Each study was appraised using the Joanna Briggs Institute Critical Appraisal Tools and analyzed through narrative synthesis. The findings revealed that psychosocial support interventions consistently improved patients’ quality of life across psychological, social, and functional domains. Family-based programs, mindfulness practices, counseling, and cognitive behavioral therapy demonstrated the most consistent positive outcomes, particularly when delivered with sufficient duration and active family involvement. Cultural and contextual adaptation further enhanced intervention effectiveness. These findings reaffirm psychosocial support as a cornerstone of holistic nursing care for individuals with degenerative diseases. Integrating psychosocial approaches into nursing practice and health policy is essential to enhance patients’ well-being, foster resilience, and promote a human-centered paradigm of care grounded in empathy, adaptation, and evidence-based practice.